The VLBA Fast Radio Transient Experiment: Progress and Early Results - Wayth, Randall; Brisken, Walter; Deller, Adam; Majid, Walid; Thompson, David; Tingay, Steven; Wagstaff, Kiri (Cambridge University Press, 2012)
Motivated by recent discoveries of isolated, dispersed radio pulses of possible extragalactic origin, we are performing a commensal search for short-duration (ms) continuum radio pulses using the Very Long Baseline Array (VLBA). The geographically separated antennæ of the VLBA make the system robust to local RFI and allow events to be verified and localised on the sky with milli-arcsec accuracy. We report sky coverage and detection limits from the experiment to date.